Characterization of 10 nm – 10 μm coal dust particles generated by simulated different cutting and drilling parameters: mass concentration distribution, number concentration distribution, and fractal dimension - Jintuo Zhu; Menglin Chen; Liang Wang; Haisong Sun; Chenghao Wang; Noor Azhar; Nkansah Benjamin Oduro (International Journal of Coal Science & Technology, 2023)
Abstract Nano-to-micron-sized coal dust can cause coal workers’ pneumoconiosis (CWP), and cutting and drilling are the main coal dust-generating processes. Based on a self-developed simulated coal cutting and drilling dust generation system, the effects of cutting parameters (tooth tip cone angle, impact angle, roller rotary speed, cutting speed) and drilling parameters (drill bit diameter, drilling speed) on the mass concentration distribution, number concentration distribution and fractal dimension of 10 nm – 10 μm coal dust were investigated. Results show that the mass concentration of 10 nm – 10 μm coal dust generated by cutting/drilling peak at 5.7 – 7.2 μm, while the number concentrations during cutting and drilling respectively peak at 60 – 90 nm and 20 – 30 nm. During both cutting and drilling processes, the generated coal dust particles in 10 – 300 nm account for > 90% of the total 10 nm – 10 μm coal particles, while PM2.5 in PM10 is generally below 18%. It is also found that smaller tooth tip cone angle, larger impact angle, lower roller rotary speed, smaller drill bit diameter, or lower drilling speed can reduce the generation of 10 nm – 10 μm coal dust with a fractal dimension of 0.94 – 1.92. This study reveals the distribution characteristics of nano- to micron-sized coal dust particles under different cutting and drilling parameters, and the research results can serve as reference for adjusting cutting and drilling parameters to lower down the 10 nm – 10 μm coal dust generation and thus prevent the CWP.